Fidelity of HIV programme implementation by community health workers in rural Mopani district, South Africa: a community survey - Nireshni Naidoo; Jean P. Railton; Sellina N. Khosa; Nthabiseng Matlakala; Gert Marincowitz; James A. McIntyre; Helen E. Struthers; Jude Igumbor; Remco P. H. Peters (BMC, 2018)
Abstract Background South Africa has implemented a community health programme delivered by community health workers (CHWs) to strengthen primary healthcare services. Provision of community Human Immunodeficiency Virus (HIV) services constitutes an important component of this programme. To support effectiveness, we assessed fidelity of HIV programme implementation by CHWs from the community's perspective in a rural South African setting. Methods A cross-sectional study was conducted targeting 900 randomly selected households in twelve wards of two sub-districts (Greater Giyani and Greater Letaba) of Mopani District (Limpopo Province, South Africa). Questionnaires were administered to the traditionally most appropriate adult member of the household. Included were questions related to the four standard components to measure implementation fidelity against local guidelines: coverage, frequency, duration and content of HIV programme implementation. Results Participants were enrolled at 534 households; in most other cases there was nobody or no adult member at home (n = 291). Reported coverage of 55% (141/253) and a frequency of 47% (66/140) were higher in Greater Giyani as compared to Greater Letaba (44%; 122/278 and 29%; 33/112, respectively, p = 0.007 for both comparisons). Coverage was not associated with the distance from the participant's household to the facility (p = 0.93). Duration of programme delivery was reported to be high, where all CHW visits (253/253; 100%) were conducted within the last 6 months and the content delivered was adequate (242/253; 96%). Individuals reporting a CHW visit were more likely to know their HIV status than those not visited (OR = 2.0; 95% CI 1.06-3.8; p = 0.032). Among those visited by the CHW discussion of HIV was associated with knowing the HIV status (OR = 2.2; 95% CI 1.02-4.6; p = 0.044); in particular for women (OR = 2.9; 95% CI 1.5-5.4; p = 0.001). Conclusions This study demonstrates promising HIV programme implementation fidelity by CHWs in rural South Africa. Programme coverage and frequency should be improved whilst maintaining the good levels of duration and content. Resource investment, strengthening of operational structure, and research to identify other facilitators of programme implementation are warranted to improve programme effectiveness and impact.